School choice, teachers’ work, and professional identity - Castro, Andrene J.; Jabbar, Huriya; Núñez Miranda, Sebastian (Education Policy Analysis Archives, 2022)
Teacher professional identity, or what it means to be a teacher, informs the types of schools teachers seek for work. With the marketization of schools in the US and abroad, teachers’ professional identities are changing. However, we know little about how teachers negotiate—and renegotiate—their professional identities during the job search in contexts with school choice, such as charter schools. This study uses qualitative interview data from 46 teachers in San Antonio, Texas, where over 25% of students attend charter schools. Our findings illuminate the job search as a critical juncture where teachers evaluate their professional identity as they make choices about the sector—charter or traditional public school—and/or school organization they prefer. In particular, the choice context legitimated flexibility and fluidity in teachers’ professional identity as teachers moved between sectors to find jobs, even if the school did not align with their personal or professional values. We also found that employability and teachers’ perception of the job market played an important role in how teachers strategically presented their professional identity on the job search. Findings offer implications for teacher education and teacher workforce policies.